PENGARUH KOMPETENSI DAN MOTIVASI KERJA GURU TERHADAP HASIL BELAJAR SISWA MADRASAH TSANAWIYAH - Anis Fauzi; Duriyat Duriyat (Institut Agama Islam Negeri Kendari, 2018)
The aim of this research is to investigate the teachers’ competence and work motivation, as well as the students' achievement. It is specific for Islam education teachers (PAI); PAI teachers’ competence and work motivation, and to determine the students’ learning outcomes at Madrasah Tsanawiyah according to KKM of MTs Negeri 1 Serang. The research instrument used are questionnaire, test and documentation. The collected data was analyzed by using quantitative data with descriptive statistics, and multiple regression analysis. After the researcher conducted the hypothesis testing, the following conclusions were obtained: First, the teachers’ competence, teachers’ work motivation, and the students’ achievement are classified as medium category. Second, there is a significant influence of PAI teachers’ competence towards the students’ achievement at Madrasah Tsanawiyah based on KKM of MTs Negeri 1 Kabupatten Serang taking up to 5.3%. Third, there is a significant influence of PAI teachers’ work motivation towards students’ achievement at Madrasah Tsanawiyah based on KKM of MTs Negeri 1 Serang as much as 15,5%. Fourth, there is a significant influence of PAI teachers’ competence and work motivation toward students' achievement at Madrasah Tsanawiyah based on KKM of MTs Negeri 1 Serang at 5.5%. Finally, it can be concluded that the influence of PAI teachers’ competence and work motivation toward students' achievement at Madrasah Tsanawiyah based on KKM of MTs Negeri 1 Serang is only 5.5%.